2016
DOI: 10.3899/jrheum.150406
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Costs for Psoriasis and Psoriatic Arthritis in a Population-based Cohort in Southern Sweden: Is It All Psoriasis-attributable Morbidity?

Abstract: Annual mean incremental societal cost per patient was highest for PsA, mainly because of productivity losses and biological treatment. A minor fraction of the costs were identified as attributable to PsO/PsA specifically, indicating an increased morbidity in these patients that needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Psoriasis is a chronic disease requiring effective long-term treatment to manage the debilitating consequences, and societal and economic burden of disease (23,24). However, drug survival data from the DERMBIO registry, which contains data on all Danish patients with moderate-to-severe psoriasis treated with biologics, indicate that the investigated biologic drugs (adalimumab, etanercept, infliximab, secukinumab, and ustekinumab) may eventually all lose efficacy ( Figure 1) (2).…”
Section: Drug Survivalmentioning
confidence: 99%
“…Psoriasis is a chronic disease requiring effective long-term treatment to manage the debilitating consequences, and societal and economic burden of disease (23,24). However, drug survival data from the DERMBIO registry, which contains data on all Danish patients with moderate-to-severe psoriasis treated with biologics, indicate that the investigated biologic drugs (adalimumab, etanercept, infliximab, secukinumab, and ustekinumab) may eventually all lose efficacy ( Figure 1) (2).…”
Section: Drug Survivalmentioning
confidence: 99%
“…According to a study by the National Psoriasis Foundation (NPF), 49% of people with psoriasis and/or PsA miss work regularly due to illness [7]. Generally, it is estimated that around 20-40% of the total costs of psoriasis are attributable to productivity and work loss [17][18][19][20][21][22]. Among patients with PsA, it has been found that work disability rates range from 23 to 39% [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study that used an employment disadvantages questionnaire to compare patients with psoriasis and PsA found an increased rate of work problems caused by PsA (32% versus 11% for psoriasis; p < 0.0005) [ 25 ]. Similarly, productivity loss has been shown to be greater among patients with PsA compared with those with other inflammatory diseases such as psoriasis, ankylosing spondylitis, rheumatoid arthritis [ 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis leads to cumulative life course impairment . In comparison with a referent cohort and a matched control group including a random mix of other diseases, psoriasis is known to produce higher costs . The economic burden for the patient and for society has been shown by several authors .…”
Section: Introductionmentioning
confidence: 99%